Demyelination, strokes, and eculizumab: Lessons from the congenital CD59 gene mutations. (September 2017) - Tabib, Adi; Karbian, Netanel; Mevorach, Dror
Highlights: Patients with p.Cys89Tyr mutation in CD59 have recurrent peripheral neuropathy and strokes. Three additional mutations in CD59 were described. Overall, 12/12 of patients with any mutation presented with neurological symptoms. CD59 is related to demyelination and thrombophilic state. Abstract: Neurological symptoms of patients with p.Cys89Tyr mutation in the CD59 gene include recurrent peripheral neuropathy resembling Guillain-Barré syndrome, characterized by sensory-motor demyelinating neuropathy with secondary axonal damage and moderate enhancement of the nerve roots on spine MRI, together with recurrent strokes and retinal involvement. Three additional mutations in CD59, leading to loss of function, have been described, and overall, 12/12 (100%) of patients with any mutation presented with neurological symptoms; 11/12 (92%) patients presented with recurrent peripheral neuropathy, 6/12 (50%) with recurrent strokes, and 1/12 (8%) with retinal involvement. We review the possible thrombophilic profile associated with the mutations. In these patients, excessive intravascular hemolysis saturates scavenger mechanisms resulting in free hemoglobin in plasma that irreversibly reacts with nitric oxide to form nitrate and methemoglobin, leading to arterial thrombosis. CD59 loss of function is also one of the major thrombophilic mechanisms in patients with paroxysmal nocturnal hemoglobinuria. We then describe the relationship with demyelination. The lack of CD59 allows uncontrolled complement amplification following low-level spontaneous-, viral-, or post viral-induced complement activation, resulting in severe demyelination in the peripheral nervous system. It is interesting, and certainly encouraging, that after 3 years, following 4 patients with Cys89Tyr mutations who are treated with eculizumab, no strokes occurred and non-permanent neurological insults underwent resolution without any new neurological exacerbations.